2019
DOI: 10.1186/s13018-019-1281-z
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic risk factor for meniscal lesion in association with ACL rupture

Abstract: Background To assess anatomic risk factors for meniscal lesions in association with acute ACL rupture. The primary hypothesis was that tibiofemoral anatomic measures will be different in those with and without concomitant meniscus tears. Methods A retrospective review of patients who underwent acute ACL reconstruction in the department was performed. All patients underwent a postoperative CT scan. The concavity and/or convexity on the femur and the tibia were measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
2
6
0
1
Order By: Relevance
“…Several parameters are related to the width of the femoral notch [ 11 , 12 ], such as the notch width (NW), bicondylar notch width (BCW), the notch width index (NWI), condyle width of the femur, tibial spine height, and intercondylar angle. However, limited prior studies evaluated the anatomical risk factors for the injury of the meniscus [ 21 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several parameters are related to the width of the femoral notch [ 11 , 12 ], such as the notch width (NW), bicondylar notch width (BCW), the notch width index (NWI), condyle width of the femur, tibial spine height, and intercondylar angle. However, limited prior studies evaluated the anatomical risk factors for the injury of the meniscus [ 21 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…An increased LFC ratio has been reported to be associated with ACL injuries and ACL reconstruction failure. 16,19,45,46 This anatomic feature could alter the gait and loading mechanics of the tibiofemoral joint and increase the length and anisometry in the anterolateral ligament complex, which might increase anterolateral rotatory laxity. 25,45,46 As suggested by Pfeiffer et al, 45,46 an increased LFC ratio, which may be more anisometric and oval shaped, might lead to increased ligamentous laxity in the lateral or anterolateral ligament complex.…”
Section: Discussionmentioning
confidence: 99%
“…In a CT scan analysis, Gaillard et al found that a greater anteroposterior length of the lateral femoral condyle with respect to the lateral tibial condyle and lesser convexity of the lateral tibial plateau were significantly associated with LMTs. As such, the lateral compartment of males were at a greater risk 24 . Several anatomic factors have been reported to have an association with LMPRTs.…”
Section: Incidence and Risk Factorsmentioning
confidence: 99%